Distribución espacial de un índice de creatividad a nivel municipal en México - Villarreal González, Amado; Flores Segovia, Miguel Alejandro; Gasca Sánchez, Francisco Manuel (El Colegio de México A.C., 2018)
This study provides a prime discussion of the creative class at a regional level in Mexico. The analysis is grounded on Florida’s 3Ts (Talent, Tolerance and Technology) from which a creative index is estimated for each municipality. The method combines a main component analysis as well as an exploratory spatial data analysis (ESDA), the latter in order to identify spatial concentrations of high (low) values of the creativity index across the geography. The results show that the creative index is concentrated in large urban centers of Mexico such as Mexico City, Guadalajara, and Monterrey. While the findings suggest a strong relationship between human capital and technology, a weak relationship was found for the bohemian class and the creative class.